PENERAPAN MODEL PEMBELAJARAN STUDENTS TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN PRESTASI BELAJAR KIMIA PADA SISWA KELAS XI MIPA 5 SEMESTE SATU SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2017/2018 - Suriti, KD. Manik (LP2M IKIP PGRI Bali, 2019)
This type of research is classroom action research. In this research, STAD type cooperative learning model is used. Research with a qualitative descriptive design with STAD type of cooperative learning model consists of two cycles including planning, implementation, observation and reflection. The subjects of this study were students of class XI MIPA 5 in SMA Negeri 7 Denpasar in the academic year 2017/2018, with a total of 40 students consisting of 19 male students and 21 female students. The object of the study was to improve chemistry learning achievement in students of class XI MIPA 5. The research was carried out at SMA Negeri 7 Denpasar Jalan Cambodia Number 9 Denpasar. Data collection in this study was carried out using test and non-test techniques. Based on the results of the research obtained in the first cycle showed of 40 students (1) the number of students whose value increased by 36 students (90%), and the value remained as many as 4 people (10%), (2) the number of students who have not completed as many as 5 people (12.5%), (3) the percentage increase in the average value of the class in learning to write exposition text by applying the STAD type cooperative learning model at initial reflection (59.56), cycle I (71.21), cycle II (81.72). The use of cooperative learning model type STAD (Student Team Achievement Division) can improve chemistry learning achievement grade XI MIPA 5 SMA Negeri 7 Denpasar.